Improving an emergency department flows through modeling and simulation - Mohamad, Fazeeda; Cheng, Jack Kie; Shamsudin, Norazidah; Safinaz, Omar; Azian, Ibrahim; Rahamaddulla, Syed Radzi (2019)
This study presents the simulation model to evaluate the treatment process of emergency department (ED). The three objectives are mainly considered, which are by identifying various procedures in ED of a general hospital, to model and evaluate resource utilization that may lead to the bottleneck as well as to propose a better configuration to the ED. ED is known as the frontline of service provider that opens 24 hours per day to serve patients that comes to their door. Regardless, with the increasing of patient’s number, hospital was keen to meet the demands in ED where the demand of services provided exceeds their ability to serve patients in an appropriate time frame. The use of Discrete Event Simulation (DES) model allows hospital administrator to understand the treatment process and detected the bottlenecks area in the process. Theory of Constraints (TOC) is also used to identify the constraints in the areas examined in ED. The results from the scenarios experimentation showed that comparison with 20% increase of patients to triage zones affects the different treatment time procedures in both green and yellow zone.